Tridax procumbens: A medicinally valuable weed - Singh, Manvendra (Indian Horticulture, 2022)
Tridax procumbens is found throughout India and have various pharmacological active compounds which allow its use as folk medicine in variety of ailments. It has been widely used in the Ayurveda due to the presence of medicinal properties for wound healing, malaria, diarrhea, dysentery, bronchial catarrh, stomach-ache and reducing blood pressure. It also prevents hair loss and haemorrhage from cuts and bruises. Its flowers and leaves possess antiseptic, insecticidal and parasiticidal properties. T. procumbens also shows various pharmacological activities. Therefore, there is a broad area of research in direction of more pharmacological activities of plant and use their properties like antimicrobial and insect repellent properties in organic farming to reducing the input cost in agriculture.